2009
DOI: 10.5194/acp-9-771-2009
|View full text |Cite
|
Sign up to set email alerts
|

Loading-dependent elemental composition of α-pinene SOA particles

Abstract: Abstract. The chemical composition of secondary organic aerosol (SOA) particles, formed by the dark ozonolysis of α-pinene, was characterized by a high-resolution time-of-flight aerosol mass spectrometer. The experiments were conducted using a continuous-flow chamber, allowing the particle mass loading and chemical composition to be maintained for several days. The organic portion of the particle mass loading was varied from 0.5 to >140 µg/m 3 by adjusting the concentration of reacted α-pinene from 0.9 to 91.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
312
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(397 citation statements)
references
References 57 publications
82
312
2
1
Order By: Relevance
“…This effective density value closely matches that determined previously from Bahreini et al (2005), Zelenyuk et al (2008), andShilling et al (2008) concentrations were approximately an order or magnitude lower than that reported here and used seed particles, while the experiments of Shilling et al had initial hydrocarbon concentrations even lower. In addition to these differences, the experiments of Shilling et al contained dry ammonium sulfate seed particles and a relative humidity of 40%.…”
Section: ␣-Pinene-ozone Soa Densitysupporting
confidence: 71%
See 1 more Smart Citation
“…This effective density value closely matches that determined previously from Bahreini et al (2005), Zelenyuk et al (2008), andShilling et al (2008) concentrations were approximately an order or magnitude lower than that reported here and used seed particles, while the experiments of Shilling et al had initial hydrocarbon concentrations even lower. In addition to these differences, the experiments of Shilling et al contained dry ammonium sulfate seed particles and a relative humidity of 40%.…”
Section: ␣-Pinene-ozone Soa Densitysupporting
confidence: 71%
“…More recently, density is reported using particle time of flight (PTOF)-SMPS and APM-SMPS comparisons (Jimenez et al 2003;Kostenidou et al 2007;McMurry et al 2002;Song et al 2007). Furthermore, recent work by Shilling et al has shown aerosol vacuum effective densities from α-pinene ozonolysis are a function of the mass loading (Shilling et al 2008). The relationship between mass loading and aerosol density is thought to arise from the relative contribution of highly oxygenated species to the total aerosol mass.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical compositions of the SOAs generated during ozonolysis and photooxidation should be somewhat different from each other, according to the literature (Jang and Kamens 1999;Iinuma et al 2004Iinuma et al , 2005Ma et al 2008;Shilling et al 2009;Noziere et al 1999;Ng et al 2007;Claeys et al 2009;Eddingsaas et al 2012). In the present study, a non-negligible value of nitrate to organic (HRNO 3 /HROrg) ratio, which was calculated from the H-ToF-AMS data, and slightly larger O/C and H/C ratios were observed for the SOAs generated by photooxidation (Table 1) compared to those for the SOAs generated by ozonolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable variability is observed in the yield of SOA generated by BVOC oxidation (e.g. Yu et al, 1999a;Kroll et al, 2006;Shilling et al, 2009). …”
Section: Gas-phase Emissions and Chemistrymentioning
confidence: 99%